2020
DOI: 10.3389/fgene.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of Long Non-coding RNA and mRNA in Sheep Mammary Gland During Lactation Period

Abstract: Sheep milk and related products have been growing in popularity around the world in recent years. However, the sheep milk industry is limited by low milk yield, and the molecular regulators of ovine lactation remain largely unknown. To investigate the transcriptomic basis of sheep lactation, RNA-Sequencing was used to explore the expression profiles of lncRNA and mRNA of the mammary gland in Hu sheep at three key time points during the lactation stage: 5 days before the expected date of parturition perinatal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Collagen, as the most abundant protein in the body, is essential for maintaining the natural structure and strength of connective tissue(Chen et al 2020 ). Glycine, proline, and hydroxyproline are the main amino acids that make up the collagen structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen, as the most abundant protein in the body, is essential for maintaining the natural structure and strength of connective tissue(Chen et al 2020 ). Glycine, proline, and hydroxyproline are the main amino acids that make up the collagen structure.…”
Section: Discussionmentioning
confidence: 99%
“…COL3A1 was found to be DEG in this study. This evidence suggests that COL3A1 may play an important role in the sheep mammary epithelial cells cycle and can be considered as a candidate hub gene for future research in cows (Chen et al 2020 ). A study evaluating various miRNAs expressed in dairy heifers and dairy cows showed that COL1A2 is one of the genes associated with the cytoskeleton and extracellular matrix and is associated with mammary gland functional activity (Wicik et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing number of reports on their involvement in host cell response (proliferation, differentiation, and apoptosis) to bacterial infections [73], as they are involved in epigenetic regulation, chromatin organization, transcriptional control, and pre-and posttranslational mRNA processing [93,94]. In addition, there have been reports about a novel mode of action of lncRNAs as competitive endogenous RNAs (ceRNAs), which affect the expression of mRNAs [95].…”
Section: Other Non-coding Rnasmentioning
confidence: 99%
“…In recent years, with the development of high-throughput sequencing, novel bioinformatics methods and related experimental validation, several classes of non-coding RNAs, such as circRNA, lncRNA and miRNA, have emerged and appear to play an important role in various biological processes (Chang et al, 2018;He et al, 2019;Chen et al, 2020;Zhou et al, 2020;Mei et al, 2021;Wu et al, 2021). CircRNA is different from linear RNA without 5 cap and 3 end poly-A tail.…”
Section: Introductionmentioning
confidence: 99%